The elements of style - Strunk, William, 1869-1946.; White, E. B.( 1899-1985.) (New York: Macmillan, 1979)
Whether you write letters, term papers, or novels, this famous manual can help you communicate more effectively.
Keywords: English language -- -- Rhetoric; Report writing; Retorica; Taalkunde; Engels; English language -- -- Style